2016
DOI: 10.5935/abc.20160072
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Implantation and Morbidity and Mortality-Related Factors: a 5-Year Experience in Brazil

Abstract: BackgroundTranscatheter aortic valve implantation has become an option for high-surgical-risk patients with aortic valve disease.ObjectiveTo evaluate the in-hospital and one-year follow-up outcomes of transcatheter aortic valve implantation.MethodsProspective cohort study of transcatheter aortic valve implantation cases from July 2009 to February 2015. Analysis of clinical and procedural variables, correlating them with in-hospital and one-year mortality.ResultsA total of 136 patients with a mean age of 83 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
5
0
3
Order By: Relevance
“…222,223 • Em outra avaliação realizada na cidade do Rio de Janeiro com 136 pacientes submetidos a TAVI [mediana de idade, 83 (80)(81)(82)(83)(84)(85)(86)(87) anos; 51% homens], a mortalidade peroperatória foi 1,5%, a mortalidade de 30 dias, 5,9%, a mortalidade hospitalar, 8,1% e a mortalidade de 1 ano, 15,5%. 224 • De 819 valvas aórticas implantadas por via percutânea até 2017, 135 pacientes (20,1%) precisaram de marca-passo permanente. Esses pacientes eram mais velhos (82,5 vs. 81,1 anos; p=0,047), predominantemente homens (59,3% vs 45%; p=0,003) e tinham bloqueio de ramo direito prévio (OR=6,19; IC 95%, 3,56 -10,75, p≤0,001).…”
Section: Implante Percutâneo De Valva Aórtica No Brasilunclassified
“…222,223 • Em outra avaliação realizada na cidade do Rio de Janeiro com 136 pacientes submetidos a TAVI [mediana de idade, 83 (80)(81)(82)(83)(84)(85)(86)(87) anos; 51% homens], a mortalidade peroperatória foi 1,5%, a mortalidade de 30 dias, 5,9%, a mortalidade hospitalar, 8,1% e a mortalidade de 1 ano, 15,5%. 224 • De 819 valvas aórticas implantadas por via percutânea até 2017, 135 pacientes (20,1%) precisaram de marca-passo permanente. Esses pacientes eram mais velhos (82,5 vs. 81,1 anos; p=0,047), predominantemente homens (59,3% vs 45%; p=0,003) e tinham bloqueio de ramo direito prévio (OR=6,19; IC 95%, 3,56 -10,75, p≤0,001).…”
Section: Implante Percutâneo De Valva Aórtica No Brasilunclassified
“…Our search identified 14 eligible studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26] including a total of 3449 patients undergoing TAVI (Table 1) and reporting early (in-hospital, 15 30-day, 17,19,23 and 3-month 20 ) and midterm (1-year, [14][15][16][17]22,25,26 600day, 13 2-year, 18,20 and 3-year 21,24 ) all-cause mortality after TAVI (Table 2). Hioki et al 20 reported data on both CRP and high-sensitive CRP (hs-CRP) form the Optimized Transcatheter Valvular Intervention (OCEAN)-TAVI registry, and we extracted the former.…”
Section: Resultsmentioning
confidence: 99%
“…18,[20][21][22]26 We converted ORs/HRs of mortality per SD (or unit) increase in CRP levels to those for high vs low CRP levels in six studies, [21][22][23][24][25][26] and vice versa in three studies. 17,19,20 In three studies, [13][14][15] SMDs in CRP levels between nonsurvivors and survivors were converted to ORs of mortality for high vs low CRP levels, from which ORs of mortality per SD increase in CRP levels were further calculated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Todas as diretrizes atuais são categóricas na indicação preferencial da TAVI em detrimento da cirurgia para pacientes inoperáveis, frágeis e/ou de alto risco cirúrgico (avaliados pelos escores STS e EuroSCORE II). [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] Entretanto, após a publicação de tais diretrizes, 4 trabalhos comparando a TAVI com a cirurgia em pacientes de baixo risco cirúrgico foram publicados. A metanálise de tais estudos demonstrou redução de mortalidade em 1 ano a favor da TAVI transfemoral.…”
Section: Estenose Aórticaunclassified